Oxytocin and HPA stress axis reactivity in postpartum women. (May 2015) - Cox, E.Q.; Stuebe, A.; Pearson, B.; Grewen, K.; Rubinow, D.; Meltzer-Brody, S.
Highlights: In a longitudinal, perinatal prospective cohort, in which a standardized stressor was administered following breastfeeding in women with and without symptoms of depression and anxiety, we found that the OT surge during breastfeeding appears to buffer subsequent stress-induced CORT secretion. Among women who breastfed at the study visit, those with affective symptoms had lower OT levels during feeding (repeated measures group p  < 0.05), and higher levels of CORT throughout the protocol (repeated measures group p  = 0.06) than women without symptoms. Heart rate response to the TSST also differed between breastfeeding women with and without symptoms (repeated measures group × time p  = 0.03). Despite similar buffering of stress-induced CORT by OT, symptomatic women experienced a positive correlation between OT AUC and CORT, instead of the expected negative correlation. Summary: Background: Lactation is thought to buffer stress reactivity via oxytocin (OT). Dysregulation of the HPA axis has been reported in women with postpartum depression (PPD). The co-occurrence of PPD and lactation failure suggests that abnormalities in OT signaling may play a role in PPD. We hypothesized that abnormal OT signaling is implicated in dysregulated HPA axis reactivity among postpartum women with mood symptoms. In a prospective perinatal cohort, we tested associations between OT levels during breastfeeding and stress reactivity. Methods: We recruited 52 pregnant women who intended to breastfeed, among whom 47 underwent a standardized stressor, the Trier Social Stress Test (TSST), at 8 weeks postpartum. 39 were breastfeeding at time of TSST. We assessed mood symptoms using validated instruments and defined as symptomatic women with EPDS ≥ 10 and/or Spielberger ≥ 34. Following IV placement for blood draws, women breastfed their infants and then underwent the TSST. Mothers' hormone responses were quantified. Results: Among symptomatic breastfeeding women ( N  = 11; asymptomatic N  = 28), we found lower OT levels during breastfeeding ( p  < 0.05) and higher CORT levels ( p  < 0.05) both during breastfeeding and the TSST, as compared to asymptomatic breastfeeding women. In a mixed effects model examining CORT reactivity by symptom group and OT AUC, we observed a paradoxical response in symptomatic breastfeeding women during the TSST (group × time × OT AUC p  < 0.05); higher OT AUC was associated with higher CORT. Conclusions: In all breastfeeding women, the surge of OT during feeding appears to buffer subsequent stress-induced CORT secretion. However, in symptomatic breastfeeding women, we found a positive correlation between OT AUC and CORT, instead of the expected negative correlation, which we found among asymptomatic women.